L’expertise CHSCT en débat - Fabien Gâche; Nicolas Spire; Louis-Marie Barnier; Sabine Fortino; Guillaume Tiffon (La Nouvelle Revue du Travail)
Enhancing other contributions found in this “Controversies” issue, which is devoted to the expertise of health and safety committees, Sabine Fortino and Guillaume Tiffon ask Nicolas Spire, Louis-Marie Barnier and Fabien Gâche to debate topics in relation to which their analyses diverge, namely how independent experts are from their customers; to what extent they legitimise union discourse; how such expertise is used; its effects on the fight to improve working conditions; the contributions and limitations of alternative approaches like action research (in terms of elected officials’ difficulties in obtaining such expertise, appropriating it and translating it into union action).